Effect of aging and rejuvenation on adhesion properties of modified asphalt binder based on AFM. (24th September 2021) - Guo, Meng; Liang, Meichen; Jiao, Yubo; Tan, Yiqiu; Yu, Jianxin; Luo, Daisong
Abstract: The adhesion between asphalt binder and aggregate is very important to the performance and durability of asphalt pavement. In order to explore the characterisation of modified asphalt binder in microstructure during aging and rejuvenation, the virgin asphalt binder and three kinds of modified asphalt binder (styrene‐butadiene‐styrene block copolymer (SBS), rubber powder and high viscosity and high elasticity [HVHE] modifier) in different aging and rejuvenation condition were prepared. The micromorphology and surface adhesion were measured by atomic force microscopy. The average roughness value was used as the index to evaluate the micromorphology of asphalt binder. The surface adhesion was used as the index to evaluate the adhesion properties of asphalt binder. Results show that the "bee" structure of SBS‐modified asphalt binder increased slightly after long‐term aging, and the recovery effect of aromatics oil was the closest to that of the unaged one. The rubber powder‐modified asphalt binder and HVHE‐modified asphalt binder showed the spot structure. And no matter for short‐term aging or long‐term aging, aromatics oil had the best recovery effect on micro morphology. The adhesion of the three modified asphalts would decrease gradually after aging. The effects of three kinds of rejuvenator on the adhesion of SBS‐modified asphalt binder and rubber powder‐modified asphalt binder were different. Rejuvenator, aromatic oil and warm mix asphalt mixture (WMA) additive could rejuvenate the loss of adhesion of HVHE‐modified asphalt binder to a certain extent.